Subsurface structural mapping of Northern Nasser Lake region, Aswan, Egypt, using Bouguer data - SALEH, Salah (Contributions to Geophysics and Geodesy, 2011)
In this study, we attempt to delineate the subsurface structures for the tectonic active region of Northern Nasser Lake using integrated interpretation techniques of gravity data with seismicity. The depths to the gravity sources, and the locations of the contacts of density contrast were estimated. Two methods were used for estimating source depths and contact locations: horizontal gradient (HG) and Euler deconvolution methods. Moreover, power spectral analysis, bandpass and upward continuation techniques were applied to evaluate the shallow and deep seated structures. Shallow depth structures were ranging between 0.30 km and 0.80 km. However, two average levels (interfaces) at depth 3.1 km and 7.2 km below the measuring level were revealed for the intermediate and deep seated structures respectively. Results of Euler deconvolution method suggested that, in the eastern part of the area, the basement could be observed on the ground and has become deeper in the central part. The interpreted structural map reveals that the area is affected by a set of faults trending mainly in the NW, E–W, N–S and NE–SW directions. Actually, this map has confirmed the idea that the intersections between the N–S and E– W striking faults along Nasser Lake area have generated seismic pulses. Moreover, three seismic zones (Z1, Z2 and Z3) are well correlated with the fault trends of the subsurface structures as derived from the horizontal gradient map. The present results suggest that there exist seismically-active fault east of High Dam, passing throughout Aswan reservoir from north to south. This fault is occupying region of high stress values which may generate large earthquakes in future, as it has long extension over several kilometers. Furthermore, the evaluated intruded volcanic bodies are found almost at the intersections between the E–W and NW oriented faults.